Assessment variability of annual daily maximum rainfall of Johor, Malaysia - Nur Farehah, Abdullah Anastas Zorin (2015)
Floods generally occur in the main settlements in Johor. Flood happened in Johor generally is characterised by the yearly alternation of Southwest and Northeast monsoons. Floods have caused roads and connection between towns cut off. This problem makes it harder for emergency teams to deliver aids quickly. This paper deals with the assessment variability of annual daily maximum rainfall of Johor area. Daily rainfall data were collected from daily satellite image, Tropical Rainfall Measuring Mission (TRMM) for 16 years (1998-2013). Descriptive statistical analysis was conducted for the three types of data i) annual rainfall ii) annual monthly maximum rainfall and iii) annual daily maximum rainfall. Gumbel distribution function was applied to estimate extreme rainfall events’ return period and found that annual daily maximum for Kluang, the city with the highest rainfall equal or greater than 535 mm had a return period of 100 years. The outcomes of this paper can be used to know the estimated rainfall depth of maximum rainfall in Johor Bahru and can be used in understanding rainfall patterns in different parts of cities in Johor. On top of that, we can have better planning of infrastructures for mitigation to cater the predicted high rainfall intensity